The Macedonian mint at Susa (319/8-312/1 BC) - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2019)
This paper details a study of the coinage of Susa struck prior to Seleukos’s annexation of the province of Susiana to Babylonia in 312/1 BC. This coinage is divided into four groups defined on the basis of a progression of mint controls and the accompanying legend. The collective evidence suggests that the first three groups of this coinage were struck simultaneously in the period c. 319/8-318/7 BC to fund the campaign of Eumenes, preceding the confrontation with Antigonos at Paraitakene and Gabiene in 317/6 BC. This represents a downdating by up to seven years of the start of the Macedonian mint at Susa relative to that proposed by Price. In contrast, the fourth group struck from a single obverse tetradrachm die, was an exceptional stand-alone issue, under the satrap Aspeisas, 317/6-312/1 BC, possibly struck immediately preceding the annexation of the province of Susiana to Babylonia by Seleukos in 312/1 BC.